A pidgeon method magnesium slag-based vitrified binding agent, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611358561.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-16
AI Technical Summary
该类渣具有一定钙镁硅质陶瓷原料基础,但若直接用于陶瓷磨具结合剂,容易存在游离CaO/MgO水化膨胀、硅酸钙类矿物活性高、低温液相形成能力不足、成分均匀性和烧成稳定性较差等问题,难以满足陶瓷磨具结合剂对软化温度、润湿性、结合强度和组织稳定性的要求
1、本申请实施例提供了一种皮江法镁渣基玻化结合剂,按质量百分比计,制备玻化结合剂的原料包括:皮江法镁冶炼渣:25%~60%,含硅原料:15%~40%,含硼原料:8%~28%,含铝原料:3%~15%,碱金属调节剂:2%~10%,玻璃结构调节剂:0%~8%,晶化调节剂:0%~5%;采用皮江法镁冶炼渣制的备玻化结合剂,既能满足市场对陶瓷模具的应用要求;又可实现皮江法镁冶炼渣的资源化利用,提高固废附加值,推动镁冶炼渣的规模化消纳与循环利用。
Smart Images

Figure CN122914054A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of abrasive and grinding material technology, and in particular to a Pidgeon process magnesium slag-based vitrified binder, its preparation method, and its application. Background Technology
[0002] Ceramic binders are a widely used type of inorganic binder in the abrasive and grinding wheel industry. They possess characteristics such as good heat resistance, good self-sharpening properties, high porosity, resistance to clogging, ease of dressing, and relatively low thermal expansion. They can be used in the preparation of abrasives such as corundum, silicon carbide, cubic boron nitride, and diamond. The chemical composition, softening temperature, high-temperature fluidity, coefficient of thermal expansion, and interfacial bonding state between the ceramic binder and the abrasive directly affect the strength, microstructure uniformity, grinding efficiency, and service life of the grinding wheel.
[0003] Pidgeon process magnesium smelting slag is a bulk solid byproduct generated during the production of metallic magnesium. It is typically a powder or fine granular material, mainly containing CaO, SiO2, MgO, and small amounts of Al2O3 and Fe2O3. The mineral phases are primarily calcium silicate, dicalcium silicate, residual magnesium oxide, and a small amount of free calcium oxide. While this type of slag has a certain basis as a calcium-magnesium-silica ceramic raw material, if directly used as a binder for ceramic abrasives, it is prone to problems such as hydration expansion of free CaO / MgO, high activity of calcium silicate minerals, insufficient low-temperature liquid phase formation ability, poor compositional uniformity, and poor firing stability. These issues make it difficult to meet the requirements of ceramic abrasive binders for softening temperature, wettability, bonding strength, and structural stability.
[0004] In view of this, it is necessary to design a Pidgeon process magnesium slag-based vitrified binder, its preparation method, and its application to solve the above problems. Summary of the Invention
[0005] This application provides a vitrified binder based on Pidgren process magnesium slag, its preparation method, and its application, in order to solve the following technical problem: how to develop a method for preparing a vitrified binder based on Pidgren process magnesium slag, taking into account the composition and phase characteristics of Pidgren process magnesium smelting slag. In a first aspect, embodiments of this application provide a Pidgeon process magnesium slag-based vitrifying binder, wherein the raw materials for preparing the vitrifying binder, by mass percentage, include: Pidgeon process magnesium smelting slag: 25%–60%, silicon-containing raw materials: 15%–40%, boron-containing raw materials: 8%–28%, aluminum-containing raw materials: 3%–15%, alkali metal modifier: 2%–10%, glass structure modifier: 0%–8%, crystallization modifier: 0%–5%.
[0006] Optionally, the Pidgeon process magnesium smelting slag is the smelting slag produced during the Pidgeon process magnesium smelting; The silicon-containing raw materials include at least one of quartz powder, silicon micro powder, waste glass powder, and borosilicate glass powder; The boron-containing raw material includes at least one of boric acid, borax, boron oxide, and boron glass powder; The aluminum-containing raw material includes at least one of kaolin, alumina, bauxite, and pyrophyllite; The alkali metal modifier includes at least one of sodium carbonate, potassium carbonate, lithium carbonate, albite, and potassium feldspar. The glass structure modifier includes at least one of zinc oxide, talc, zirconium silicate, and calcium carbonate; The crystallization regulator includes at least one of zirconium oxide, titanium oxide, cerium oxide, lanthanum oxide, and yttrium oxide.
[0007] Optionally, by mass percentage, the oxide composition of the vitrified binder includes: SiO2: 35%–55%, B2O3: 8%–25%, Al2O3: 3%–15%, CaO: 10%–30%, MgO: 3%–15%, Na2O+K2O+Li2O: 1%–12%, ZnO+ZrO2+TiO2+rare earth oxides: 0%–10%, Fe2O3≤5%.
[0008] Secondly, embodiments of this application provide a method for preparing the Pidgeon process magnesium slag-based vitrified binder described in the first aspect, comprising the following steps: The Pidgeon process magnesium smelting slag is subjected to crushing, homogenization and drying processes in sequence to obtain magnesium slag pretreated material; The magnesium slag pretreated material, the silicon-containing raw material, the boron-containing raw material, the aluminum-containing raw material, and the alkali metal regulator are mixed to obtain a vitrified binder compound. The vitrified binder batch is melted to obtain calcium magnesium silicon borosilicate glass melt; The calcium-magnesium-silicon-boron-aluminum glass melt is vitrified to obtain a vitrified material; The vitrified material is dried, ground, and classified in sequence to obtain the Pidgeon process magnesium slag-based vitrified binder.
[0009] Optionally, before performing the melt treatment on the vitrified binder batch, the glass structure modifier and / or the crystallization modifier may be added to the vitrified binder batch.
[0010] Optionally, the melting process includes: heating the vitrified binder compound to 1250℃~1500℃ at a heating rate of 3℃ / min~10℃ / min, and melting it at a constant temperature of 1250℃~1500℃ for 30min~180min.
[0011] Optionally, the drying temperature is 80℃~150℃; the drying time is 4h~12h.
[0012] Optionally, the particle size of the magnesium slag pretreated material is ≤0.5 mm, and the moisture content of the magnesium slag pretreated material is <1%.
[0013] Optionally, the vitrification process includes: The calcium magnesium silicon boron aluminum glass melt is subjected to water quenching and rapid cooling treatment to obtain the vitrified material; Alternatively, the calcium-magnesium-silicon-boron-aluminum glass melt can be subjected to pressing, rapid cooling, and crushing processes in sequence to obtain the vitrified material.
[0014] Optionally, the particle size D50 of the Pidgeon process magnesium slag-based vitrified binder is 3μm to 20μm, and the particle size D90 is ≤45μm.
[0015] Thirdly, embodiments of this application provide the application of the Pidgeon process magnesium slag-based vitrified binder described in the first aspect in the preparation of ceramic molds. The method for using the Pidgeon process magnesium slag-based vitrified binder to prepare ceramic molds includes the following steps: The vitrified binder, abrasive, and temporary binder are mixed to obtain a mixture; The mixture is sequentially pressed and dried to obtain a dried blank. The dried blank is then calcined to obtain a ceramic abrasive.
[0016] Optionally, the calcination process includes: heating the dried blank to 850℃~1100℃ and holding it at a constant temperature of 850℃~1100℃ for 1h~4h.
[0017] Optionally, the mass of the vitrified binder is 6% to 25% of the mass of the abrasive.
[0018] Optionally, the mass of the temporary binder is 1% to 5% of the mass of the abrasive.
[0019] Optionally, the abrasive includes at least one of corundum abrasive and silicon carbide abrasive.
[0020] Optionally, the temporary binder includes at least one of dextrin, polyvinyl alcohol, carboxymethyl cellulose, and lignin sulfonate.
[0021] The technical solutions provided in this application have the following advantages compared with the prior art: 1. This application provides a vitrified binder based on Pidgeon process magnesium slag. The raw materials for preparing the vitrified binder, by mass percentage, include: Pidgeon process magnesium smelting slag: 25%–60%, silicon-containing raw materials: 15%–40%, boron-containing raw materials: 8%–28%, aluminum-containing raw materials: 3%–15%, alkali metal modifier: 2%–10%, glass structure modifier: 0%–8%, and crystallization modifier: 0%–5%. The vitrified binder prepared using Pidgeon process magnesium smelting slag can meet market requirements for ceramic molds and also realize the resource utilization of Pidgeon process magnesium smelting slag, increase the added value of solid waste, and promote the large-scale consumption and recycling of magnesium smelting slag.
[0022] 2. This application also provides a method for preparing a vitrified binder based on Pidgren process magnesium slag. The method involves using Pidgren process magnesium smelting slag as a calcium-magnesium-silica base raw material, which is then mixed and tempered with silicon-containing raw materials, boron-containing raw materials, aluminum-containing raw materials, and an alkali metal modifier. High-temperature melting treatment is then performed to completely dissolve all crystalline mineral phases introduced by the Pidgren process magnesium smelting slag in the raw material at the atomic scale, homogenizing it with other tempering components into a homogeneous glass melt. Next, vitrification treatment is performed, and rapid cooling causes the high-temperature melt to quickly cross the crystallization temperature range and freeze into a long-range disordered homogeneous glassy solid. At this point, the hydration-active free CaO and free MgO in the original Pidgren process magnesium smelting slag have been converted into CaO. 2+ and Mg 2+ The ionic form of the material is firmly fixed in the interstices of the silicon-oxygen tetrahedral network as a network modifier, thus losing its independent existence and completely eliminating the risk of hydration expansion. Specifically, the original high-melting-point ternary system of CaO-MgO-SiO2 in the Pidgeon process magnesium smelting slag is reconstructed into a multi-element eutectic system of CaO-MgO-SiO2-Al2O3-B2O3-R2O. The B2O3 introduced by the boron-containing raw material can reduce the degree of polymerization of the glass network and weaken the connectivity of the silicon-oxygen tetrahedra. The R2O introduced by the alkali metal regulator can provide free oxygen to break the Si-O bond and BO bond. The synergistic effect of the boron-containing raw material and the alkali metal regulator reduces the liquid phase generation temperature of the system to 850℃~1100℃, which falls into the firing temperature range of ceramic molds. At the same time, the Al2O3 introduced by the aluminum-containing raw material enters the network skeleton in the form of aluminum-oxygen tetrahedra to enhance the structural stability, and the silicon-containing raw material supplements SiO2 to improve the network skeleton and regulate the acidity coefficient.
[0023] 3. This application also provides an application of a Pidgeon process magnesium slag-based vitrified binder. The above-mentioned Pidgeon process magnesium slag-based vitrified binder is mixed with abrasive and temporary binder and then calcined. During the calcination process, the vitrified binder undergoes secondary viscous flow, forming continuous binding necks between abrasive particles. After cooling, it solidifies into a three-dimensional network skeleton to achieve a firm hold on the abrasive, thereby transforming the Pidgeon process magnesium smelting slag from an uncontrollable active solid waste into a functional vitrified binder with controllable composition and stable performance. Attached Figure Description
[0024] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0025] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a schematic flowchart illustrating a method for preparing a Pidgeon process magnesium slag-based vitrified binder, as provided in an embodiment of this application. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0028] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the content, amount added, etc., mentioned herein are based on mass; for example, an addition amount of 1% means that the additive accounts for 1% of the total mass of the system; a content of 10% means that the component has a mass fraction of 10% in the composition. Unless otherwise specified, the terms "comprising," "including," etc., used herein mean "including but not limited to"; relational terms such as "first," "second," etc., are used only to distinguish different entities or operations and do not imply an actual order or relationship; "and / or" indicates that multiple situations can exist alone or simultaneously; expressions such as "at least one," "multiple," "at least one," etc., refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships mentioned in this article, such as mass ratio and molar ratio, should be understood as the correspondence between the antecedent and consequent of a proportional equation, according to the order in which they are described. All raw materials, reagents, instruments, and equipment used in this article can be purchased commercially or prepared using existing methods.
[0029] In a first aspect, embodiments of this application provide a Pidgeon process magnesium slag-based vitrifying binder, wherein the raw materials for preparing the vitrifying binder, by mass percentage, include: Pidgeon process magnesium smelting slag: 25%–60%, silicon-containing raw materials: 15%–40%, boron-containing raw materials: 8%–28%, aluminum-containing raw materials: 3%–15%, alkali metal modifier: 2%–10%, glass structure modifier: 0%–8%, crystallization modifier: 0%–5%.
[0030] Pidgeon process magnesium smelting slag is a bulk solid byproduct generated during the production of metallic magnesium using the Pidgeon process. The Pidgeon process is a silicothermic reduction process that uses calcined dolomite as raw material, ferrosilicon as a reducing agent, and fluorite as a mineralizing agent. Magnesium oxide is reduced to metallic magnesium vapor under high-temperature vacuum conditions. The reduction reaction equation is as follows: 2MgO·CaO(solid) + Si(solid) → 2Mg(g) + Ca2SiO4(solid) The magnesium vapor generated by the reaction is condensed to obtain crude magnesium, and the remaining solid residue is the slag from the Pidgeon process magnesium smelting.
[0031] Pidgeon process magnesium smelting slag is typically in powder or fine granular form. Its main chemical components are calcium oxide, silicon dioxide, and magnesium oxide, with small amounts of aluminum oxide and iron oxide. The calcium in the magnesium slag mainly exists in the form of dicalcium silicate (Ca2SiO4). Dicalcium silicate undergoes a crystal transformation during cooling, making the magnesium slag prone to pulverization.
[0032] This application provides a Pidgeon process magnesium slag-based vitrifying binder. In the raw materials, Pidgeon process magnesium smelting slag serves as the calcium-magnesium-silica base material, providing CaO, MgO, and a portion of SiO2 components to the vitrifying binder. CaO and MgO are both alkaline earth metal oxides, acting as network modifiers in the glass structure. They can break the bridging oxygen bonds in the silicon-oxygen tetrahedral network, reducing the degree of polymerization and high-temperature viscosity of the glass network, which is beneficial for lowering the softening temperature and high-temperature fluidity of the vitrifying binder. Simultaneously, a reasonable content of CaO and MgO can improve the interfacial chemical compatibility between the vitrifying binder and the abrasive, promoting the formation of a strong chemical bond interface between them. The minimum amount of Pidgeon process magnesium smelting slag is 25%, ensuring that it dominates all raw materials, thereby achieving large-scale disposal of bulk solid waste while ensuring that the amount of CaO and MgO introduced is sufficient to function as a network modifier and interfacial compatibility regulator. The maximum usage of Pidgeon process magnesium smelting slag is 60%. This maximum value controls the content of harmful impurities such as Fe2O3, free CaO, and free MgO introduced by the Pidgeon process magnesium smelting slag within an acceptable range. This avoids adverse phenomena such as decreased chemical stability of the vitrified binder based on Pidgeon process magnesium slag, darkening of the firing color, and high-temperature foaming caused by excessive impurities. At the same time, it also leaves sufficient room for the addition of conditioning components such as silicon-containing raw materials, boron-containing raw materials, aluminum-containing raw materials, and alkali metal regulators.
[0033] Silicon-containing raw materials refer to minerals or industrial materials that can introduce SiO2 components into the raw material. SiO2 is the core component of the glass network forging, forming a three-dimensional silicon-oxygen tetrahedral network framework in the glass structure. This framework endows the vitrified binder with the necessary structural strength, chemical durability, and thermal stability. Silicon-containing raw materials act as silicon supplements in the raw material, compensating for the insufficient SiO2 content in the Pidgeon process magnesium smelting slag, and regulating the final SiO2 composition of the vitrified binder to the optimal glass-forming range. The lower limit for the amount of silicon-containing raw material used is 15%, ensuring that the amount of SiO2 introduced is sufficient to construct a continuous and stable silicon-oxygen tetrahedral network framework. If the amount of silicon-containing raw material is less than 15%, the network framework of the vitrified binder is incomplete, the glass-forming ability is insufficient, it is prone to crystallization during melting and cooling, and the resulting vitrified binder has low mechanical strength. The maximum amount of silicon-containing raw materials is 40%. This limit controls the amount of SiO2 introduced within a reasonable range, preventing excessively high SiO2 content from causing excessively high melting temperatures and high-temperature vitrification of the vitrified binder, which would prevent it from softening and spreading sufficiently at the mold firing temperature. If the amount of silicon-containing raw materials exceeds 40%, the softening temperature of the vitrified binder will be too high, making it difficult to achieve effective bonding within the mold firing temperature range of 850℃ to 1100℃. At the same time, the relative content of network modifiers such as CaO and MgO will be diluted, weakening the effect of reducing the melting temperature.
[0034] Boron-containing raw materials refer to minerals or industrial materials that can introduce B2O3 components into the raw materials. Within the composition range of vitrified binders, B2O3 mainly acts as a flux, significantly reducing the softening temperature and high-temperature viscosity of the Pidgeon process magnesia slag-based vitrified binder, enabling the vitrified binder to produce sufficient glass liquid phase under medium-low temperature conditions of 850℃ to 1100℃. Boron-containing raw materials act as boron introducers in the raw materials, introducing B2O3 to lower the liquidus temperature and high-temperature viscosity of the Pidgeon process magnesia slag-based vitrified binder. The lower limit for the amount of boron-containing raw materials is 8%, ensuring that the amount of B2O3 introduced is sufficient to significantly reduce the high-temperature viscosity and softening temperature of the vitrified binder. If the amount of boron-containing raw materials is less than 8%, the fluxing effect of B2O3 is insufficient, the fluidity of the vitrified binder at the mold firing temperature is insufficient, and it cannot spread evenly and fully wet the abrasive. The maximum amount of boron-containing raw materials is 28%. This limit controls the introduction of B2O3 within the glass-forming region, preventing a decrease in the chemical stability and moisture resistance of the Pidgeon process magnesium slag-based vitrified binder due to excessive B2O3 content, as well as severe volatilization during melting. If the amount of boron-containing raw materials exceeds 28%, the glass network of the vitrified binder will depolymerize excessively, significantly deteriorating the mechanical strength, wear resistance, and durability of the binder. Simultaneously, boron volatilization during melting will intensify, causing compositional fluctuations and environmental pollution.
[0035] Aluminum-containing raw materials refer to minerals or industrial materials that can introduce Al2O3 components into the raw materials. Within the composition range of vitrified binders, Al2O3 mainly functions to strengthen the network skeleton and improve the mechanical strength and chemical stability of the vitrified binder. Aluminum-containing raw materials act as aluminum modifiers in the raw materials, introducing Al2O3 to enhance the network skeleton and chemical durability of the vitrified binder. The lower limit of the amount of aluminum-containing raw materials is 3%, which ensures that the amount of Al2O3 introduced is sufficient to strengthen the network and inhibit crystallization. If the amount of aluminum-containing raw materials is less than 3%, the network structure strength of the vitrified binder is insufficient, making it prone to crystallization during cooling after high-temperature firing, and the mechanical strength and hydration resistance of the binder are low. The upper limit of the amount of aluminum-containing raw materials is 15%, which controls the amount of Al2O3 introduced within a reasonable range, avoiding excessively high melting temperature and high-temperature viscosity of the Pidgeon process magnesium slag-based vitrified binder due to excessive Al2O3 content. If the amount of aluminum-containing raw materials exceeds 15%, then Al2O3 is excessive, the network structure of the vitrified binder is too dense, the viscosity at high temperature increases significantly, and it is difficult to flow and wet the abrasive at the mold firing temperature.
[0036] Alkali metal modifiers are mineral or industrial materials that can introduce alkali metal oxides (Na₂O, K₂O, or Li₂O) into raw materials. Alkali metal oxides act as network modifiers in glass structures, providing free oxygen to break silicon-oxygen and boron-oxygen bonds, reducing the degree of polymerization of the glass network, and significantly lowering the softening temperature and high-temperature viscosity of the vitrified binder. Alkali metal modifiers also act as alkali control agents in raw materials, introducing alkali metal oxides to synergistically reduce the melting temperature and high-temperature viscosity of the vitrified binder, and adjusting the coefficient of thermal expansion. The minimum dosage of alkali metal modifiers is 2%, which ensures that the amount of alkali metal oxides introduced is sufficient to produce a noticeable fluxing effect. If the dosage of alkali metal modifiers is less than 2%, the amount of alkali metal oxides introduced is insufficient, the softening temperature and high-temperature viscosity of the vitrified binder are too high, and the amount of liquid phase generated at the mold firing temperature is insufficient. The maximum amount of alkali metal modifier is 10%. This maximum amount controls the total amount of alkali metal oxides introduced within a reasonable range, avoiding excessive thermal expansion coefficient, decreased chemical stability, and excessive reduction in high-temperature viscosity of the vitrified binder due to excessive alkali metal oxide content.
[0037] Glass structure modifiers play a role in optimizing the glass network structure and regulating high-temperature rheological behavior in vitrified binders. Glass structure modifiers are optional components in the raw materials; a mass percentage of 0% indicates that this component is not added. The maximum dosage of glass structure modifiers is 8%. This upper limit ensures that the glass structure modifier serves only as an auxiliary regulating component and does not alter the basic glass system of the Pidgeon process magnesia slag-based vitrified binder. If the dosage of glass structure modifiers exceeds 8%, the composition of the Pidgeon process magnesia slag-based vitrified binder deviates from the basic glass-forming region, potentially leading to increased crystallization tendency, liquid phase separation, or performance degradation.
[0038] Crystallization regulators in vitrified binders play a role in controlling the precipitation behavior and crystallite size of the microcrystalline phase, ensuring the formation of an appropriate amount of microcrystalline phase during the firing of ceramic molds. This microcrystalline phase enhances the binder's strength, wear resistance, and thermal shock resistance. Crystallization regulators are optional auxiliary components; a mass percentage of 0% indicates that this component is not added. The maximum dosage of crystallization regulators is 5%. This maximum ensures that the crystallization regulator acts solely as a crystallization behavior regulator and does not cause excessive crystallization of the Pidgeon process magnesia slag-based vitrified binder during melting and cooling or mold firing. If the dosage of crystallization regulators exceeds 5%, the Pidgeon process magnesia slag-based vitrified binder will exhibit an excessive tendency to crystallize, resulting in the precipitation of a large number of crystals during melting and cooling, causing the binder to lose its glassy properties and severely reducing its fluidity and wettability.
[0039] In some embodiments, the Pidgeon process magnesium smelting slag is a powdery or fine-granular smelting slag produced during the Pidgeon process magnesium smelting. The silicon-containing raw materials include at least one of quartz powder, silicon micro powder, waste glass powder, and borosilicate glass powder; The boron-containing raw material includes at least one of boric acid, borax, boron oxide, and boron glass powder; The aluminum-containing raw material includes at least one of kaolin, alumina, bauxite, and pyrophyllite; The alkali metal modifier includes at least one of sodium carbonate, potassium carbonate, lithium carbonate, albite, and potassium feldspar.
[0040] Silicon-containing raw materials are all mainly composed of silicon dioxide, which is widely available and has a low cost.
[0041] The boron-containing raw materials are selected from at least one of boric acid, borax, boron oxide, and borosilicate glass powder. Boric acid and borax decompose into boron oxide at high temperatures and enter the glass network; boron oxide can directly participate in glass formation; borosilicate glass powder has the dual function of supplementing silicon and attracting boron.
[0042] In some embodiments, the glass structure modifier includes at least one of zinc oxide, talc, zirconium silicate, and calcium carbonate; the crystallization modifier includes at least one of zirconium oxide, titanium oxide, cerium oxide, lanthanum oxide, and yttrium oxide.
[0043] Glass structure modifiers focus on adjusting the network structure and basic properties of the glass. Zinc oxide adjusts the coefficient of thermal expansion and chemical stability, talc introduces magnesium oxide and silicon dioxide, zirconium silicate introduces zirconium oxide and silicon dioxide and improves abrasion resistance, and calcium carbonate supplements calcium oxide. The active components of glass structure modifiers enter the glass network or are distributed in the network gaps during the molten stage, becoming part of the glass matrix.
[0044] Crystallization regulators focus on regulating the crystallization behavior of glass during firing. Zirconia and titanium dioxide provide crystal nucleation sites, while rare earth oxides alter the activation energy for crystallization. The active components of the crystallization regulator play a role during the firing stage, determining whether the glass crystallizes, when it crystallizes, what type of crystals precipitate, and the size and distribution of the crystals.
[0045] In some embodiments, the oxide composition of the vitrified binder, by mass percentage, includes: SiO2: 35%–55%, B2O3: 8%–25%, Al2O3: 3%–15%, CaO: 10%–30%, MgO: 3%–15%, Na2O+K2O+Li2O: 1%–12%, ZnO+ZrO2+TiO2+rare earth oxides: 0%–10%, Fe2O3≤5%.
[0046] The composition of this oxide is not the raw material ratio, but the chemical composition of the final product after the vitrification binder is melted and vitrified. This composition range ensures that the vitrification binder has suitable glass-forming ability, low softening temperature and high fluidity, a coefficient of thermal expansion that matches the abrasive, and sufficient mechanical strength and chemical stability.
[0047] Figure 1 This is a schematic flowchart illustrating a method for preparing a Pidgeon process magnesium slag-based vitrified binder, as provided in an embodiment of this application.
[0048] Please see Figure 1 Secondly, embodiments of this application provide a method for preparing the Pidgeon process magnesium slag-based vitrified binder described in the first aspect, comprising the following steps: S1. The Pidgeon process magnesium smelting slag is sequentially crushed, homogenized, and dried to obtain magnesium slag pretreated material. S2. The magnesium slag pretreated material, the silicon-containing raw material, the boron-containing raw material, the aluminum-containing raw material and the alkali metal regulator are mixed to obtain a vitrified binder compound. S3. The vitrified binder batch is melted to obtain calcium magnesium silicon borosilicate glass melt; S4. Vitrify the calcium-magnesium-silicon-boron-aluminum glass melt to obtain a vitrified material; S5. The vitrified material is dried, ground and classified in sequence to obtain the Pijang process magnesium slag-based vitrified binder.
[0049] Before use, the slag from the Pidgeon process magnesium smelting must be crushed, homogenized, and dried to remove moisture, eliminate batch variations, and control particle size to meet the feeding requirements of subsequent melting processes.
[0050] In some embodiments, the glass structure modifier and / or the crystallization modifier are added to the vitrified binder batch before the melt treatment of the vitrified binder batch.
[0051] In some embodiments, the melting process includes heating the vitrified binder compound to 1250°C to 1500°C at a heating rate of 3°C / min to 10°C / min, and melting it at a constant temperature of 1250°C to 1500°C for 30 min to 180 min.
[0052] In some embodiments, the drying temperature is 80°C to 150°C; the drying time is 4 hours to 12 hours.
[0053] In some embodiments, the particle size of the magnesium slag pretreated material is ≤0.5 mm, and the moisture content of the magnesium slag pretreated material is <1%.
[0054] These two parameters together ensure that the pretreated magnesium slag material has excellent mixing uniformity, melting reactivity and melt quality, providing a basic raw material guarantee for the preparation of high-quality Pidgeon process magnesium slag-based vitrified binders.
[0055] In some embodiments, the vitrification process includes: The calcium magnesium silicon boron aluminum glass melt is subjected to water quenching and rapid cooling treatment to obtain the vitrified material; Alternatively, the calcium-magnesium-silicon-boron-aluminum glass melt can be subjected to pressing, rapid cooling, and crushing processes in sequence to obtain the vitrified material.
[0056] Rapid quenching involves pouring molten calcium magnesium silicate borosilicate glass onto cooled metal rollers or plates, where it is rapidly spread into thin sheets by rolling or pressing while simultaneously cooling. In rapid quenching, the sheet-like molten glass has a large heat dissipation area, enabling rapid cooling and solidification into glassy flakes. After rapid quenching, glassy flakes or glassy fragments are obtained. Crushing involves further breaking the glassy flakes or fragments obtained from rapid quenching into smaller sizes using mechanical methods.
[0057] In some embodiments, the particle size D50 of the Pidgeon process magnesium slag-based vitrified binder is 3μm to 20μm, and the D90 is ≤45μm.
[0058] In some embodiments, the particle size of the Pidgeon process magnesium slag-based vitrified binder is ≤45μm.
[0059] D50 refers to the particle size value corresponding to a cumulative volume distribution of 50% for the vitrified binder. It is the median diameter of the vitrified binder particle size and represents the average particle size level of the vitrified binder. D90 refers to the particle size value corresponding to a cumulative volume distribution of 90% for the vitrified binder and represents the level of coarse-end particle size control of the vitrified binder.
[0060] Thirdly, embodiments of this application provide the application of the Pidgeon process magnesium slag-based vitrified binder described in the first aspect in the preparation of ceramic molds. The method for using the Pidgeon process magnesium slag-based vitrified binder to prepare ceramic molds includes the following steps: The vitrified binder, abrasive, and temporary binder are mixed to obtain a mixture; The mixture is sequentially pressed and dried to obtain a dried blank. The dried blank is then calcined to obtain a ceramic abrasive.
[0061] In some embodiments, the calcination process includes heating the dried blank to 850°C to 1100°C and holding it at a constant temperature of 850°C to 1100°C for 1 hour to 4 hours.
[0062] In some embodiments, the mass of the vitrified binder is 6% to 25% of the mass of the abrasive.
[0063] In some embodiments, the mass of the temporary binder is 1% to 5% of the mass of the abrasive.
[0064] Temporary binders are organic adhesives added during the forming process of ceramic mold blanks. Their function is to provide sufficient wet strength and plasticity to the blank during the pressing stage, ensuring the blank maintains its shape during pressing. During the drying stage, after the moisture in the temporary binder evaporates, it acts as a temporary bond between the particles, preventing the dried blank from cracking or breaking during handling and kiln loading. During the firing stage, the temporary binder decomposes and volatilizes at a relatively low temperature, leaving no residue in the final mold product.
[0065] In some embodiments, the abrasive includes at least one of corundum abrasive and silicon carbide abrasive.
[0066] Abrasive is a hard particulate material in ceramic grinding tools that performs cutting and grinding functions. It is dispersed in the binder matrix as aggregate in the grinding tool.
[0067] In some embodiments, the temporary binder includes at least one of dextrin, polyvinyl alcohol, carboxymethyl cellulose, and lignin sulfonate.
[0068] Dextrin, polyvinyl alcohol, carboxymethyl cellulose, and lignin sulfonate are all water-soluble organic binders. Water needs to be added during the mixing process to dissolve or disperse the temporary binder and make the mixture plastic.
[0069] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national / industry standards; if there is no corresponding national / industry standard, they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.
[0070] Example 1 This embodiment provides a method for preparing a Pidgeon process magnesium slag-based vitrified binder, which specifically includes the following steps: The Pidgeon process magnesium smelting slag was crushed and homogenized to reduce its particle size to less than 0.5 mm, and then dried at 105℃ for 6 hours to obtain magnesium slag pretreated material. The above-mentioned magnesium slag pretreated material, quartz powder, boric acid, sodium feldspar, kaolin and zinc oxide were placed in a mixer and dry-mixed for 2 hours to obtain the vitrified binder batch material; wherein, the mass ratio of Pidgeon process magnesium smelting slag, quartz powder, boric acid, sodium feldspar, kaolin and zinc oxide was 30:32:18:12:6:2. The vitrified binder batch is placed in a corundum crucible and heated to 1400℃ in air atmosphere, and held for 60 minutes to fully melt and homogenize the vitrified binder batch to obtain calcium magnesium silicon borosilicate glass melt. The uniformly molten glass is rapidly poured into water for water quenching and rapid cooling to obtain vitrified material; The vitrified material was dried at 120℃ for 8 hours, then ball-milled for 24 hours, and passed through a 325-mesh sieve to obtain the Pidgeon process magnesium slag-based vitrified binder.
[0071] The measured oxide composition (mass percentage) of the vitrified binder obtained in this embodiment is as follows: SiO2 54.8%, B2O3 10.8%, Al2O3 6.4%, CaO 18.0%, MgO 4.0%, Na2O+K2O+Li2O 1.6%, ZnO+ZrO2+TiO2+rare earth oxides 2.2%, Fe2O3 0.7%.
[0072] Example 2 This embodiment provides a method for preparing a Pidgeon process magnesium slag-based vitrified binder, which specifically includes the following steps: The Pidgeon process magnesium smelting slag was crushed and homogenized to reduce its particle size to less than 0.5 mm, and then dried at 105℃ for 6 hours to obtain magnesium slag pretreated material. The above-mentioned magnesium slag pretreated material, quartz powder, boric acid, sodium feldspar, alumina, sodium carbonate and zirconium oxide were placed in a mixer and dry-mixed for 2 hours to obtain the vitrified binder batch material; wherein, the mass ratio of Pidgeon process magnesium smelting slag, quartz powder, boric acid, sodium feldspar, alumina, sodium carbonate and zirconium oxide was 40:25:15:10:5:3:2. The vitrified binder batch is placed in a melting furnace and heated to 1420℃ in an air atmosphere. It is held for 75 minutes to fully melt and homogenize the vitrified binder batch, thus obtaining calcium magnesium silicon borosilicate glass melt. The uniformly molten glass is rapidly poured into water for water quenching and rapid cooling to obtain vitrified material; The vitrified material was dried at 100°C for 10 hours, and then ball-milled to D. 90 ≤45μm, to obtain Pidgeon process magnesium slag-based vitrified binder.
[0073] The measured oxide composition (mass percentage) of the vitrified binder obtained in this embodiment is as follows: SiO2 42.1%, B2O3 10.5%, Al2O3 8.6%, CaO 22.3%, MgO 4.9%, Na2O+K2O+Li2O 7.7%, ZnO+ZrO2+TiO2+rare earth oxides 2.0%, Fe2O3 0.8%.
[0074] The vitrified binder obtained in this embodiment was subjected to high-temperature microscopic performance testing. The results showed that the softening temperature of the vitrified binder was 652℃, the hemispherical temperature was 728℃, and the flow temperature was 792℃. With increasing temperature, the vitrified binder gradually softened, spread, and exhibited viscous flow, forming a distinct liquid phase above 850℃. Therefore, at the ceramic abrasive firing temperature of 980℃, this vitrified binder possesses sufficient high-temperature flow capability and can form continuous bonding bridges between abrasive grains.
[0075] Example 3 This embodiment provides a method for preparing a Pidgeon process magnesium slag-based vitrified binder, which specifically includes the following steps: The Pidgeon process magnesium smelting slag was crushed and homogenized to reduce its particle size to less than 0.5 mm, and then dried at 110℃ for 6 hours to obtain magnesium slag pretreated material. The above-mentioned magnesium slag pretreated material, quartz powder, boric acid, sodium feldspar, kaolin, titanium oxide and cerium oxide were mixed and wet ball-milled for 4 h, and then dried to obtain the vitrified binder compound; wherein, the mass ratio of Pidgeon process magnesium smelting slag, quartz powder, boric acid, sodium feldspar, kaolin, titanium oxide and cerium oxide was 50:20:16:8:4:1:2. The vitrified binder batch is placed in a high-temperature melting furnace and heated to 1450°C in an air atmosphere. The temperature is held for 90 minutes to allow the vitrified binder batch to fully melt and homogenize, thus obtaining calcium magnesium silicon borosilicate glass melt. The uniformly molten glass is rapidly poured into water for water quenching and rapid cooling to obtain vitrified material; The vitrified material was dried at 120°C for 8 hours, and then ball-milled for 24 hours to obtain D. 50 8–15 μm, D 90 Pidgeon process magnesium slag-based vitrified binder with a thickness of ≤45μm.
[0076] The measured oxide composition (mass percentage) of the vitrified binder obtained in this embodiment is as follows: SiO2 42.6%, B2O 39.7%, Al2O 35.5%, CaO 29.7%, MgO 6.5%, Na2O+K2O+Li2O 1.5%, ZnO+ZrO2+TiO2+rare earth oxides 2.2%, Fe2O 31.1%.
[0077] The softening temperature of the vitrified binder obtained in this embodiment is 681°C, the hemispherical temperature is 754°C, and the flow temperature is 818°C.
[0078] Example 4 This embodiment provides a method for preparing a Pidgeon process magnesium slag-based vitrified binder, which specifically includes the following steps: The Pidgeon process magnesium smelting slag was crushed and homogenized to reduce its particle size to less than 0.5 mm, and then dried at 105℃ for 6 hours to obtain magnesium slag pretreated material. The above-mentioned magnesium slag pretreated material, waste borosilicate glass powder, quartz powder, boric acid, albite, pyrophyllite and zirconium silicate were placed in a mixer and dry-mixed for 2 hours to obtain the vitrified binder batch material; wherein, the mass ratio of Pidgeon process magnesium smelting slag, waste borosilicate glass powder, quartz powder, boric acid, albite, pyrophyllite and zirconium silicate was 35:30:12:8:8:5:2. The vitrified binder batch is placed in a corundum crucible and heated to 1380℃ in air atmosphere, and held for 60 minutes to fully melt and homogenize the vitrified binder batch to obtain calcium magnesium silicon borosilicate glass melt. The uniformly molten glass is rapidly poured into water for water quenching and rapid cooling to obtain vitrified material; The vitrified material was dried at 120℃ for 6 hours, then ball-milled for 24 hours and passed through a 325-mesh sieve to obtain the Pijang process magnesium slag-based vitrified binder.
[0079] The measured oxide composition (mass percentage) of the vitrified binder obtained in this embodiment is as follows: SiO2 53.7%, B2O 39.4%, Al2O 36.1%, CaO 20.0%, MgO 4.4%, Na2O+K2O+Li2O 3.2%, ZnO+ZrO2+TiO2+rare earth oxides 1.4%, Fe2O 30.7%.
[0080] Example 5 This embodiment provides a method for preparing ceramic abrasives using Pidgeon process magnesium slag-based vitrified binders, including the following steps: Provide the vitrified binder obtained in Example 2; Take 100 parts of white fused alumina abrasive, 12 parts of vitrified binder, 2 parts of dextrin (temporary binder), and an appropriate amount of water by weight, mix them evenly to obtain a mixture. After the mixture is pressed into shape, it is dried at 80℃ for 12 h to obtain a dried green body. The dried blank is placed in a kiln and kept at 980℃ for 2 hours; then cooled to room temperature in the kiln to obtain ceramic molds.
[0081] The ceramic abrasive obtained in this embodiment has a complete appearance, without cracks or deformation.
[0082] The flexural strength of the obtained ceramic abrasive was determined to be 78.5 MPa using the three-point bending method; its hardness was measured to be HRB 88.6 using a Rockwell hardness tester; and its bulk density was determined to be 2.48 g / cm³ using the Archimedes method. 3 The apparent porosity is 33.4%; the average linear expansion coefficient, measured by a thermal dilatometer, is 7.4 × 10⁻⁶ over the range of room temperature to 800℃.-6 / ℃; This ceramic abrasive exhibited good self-sharpening properties and grinding efficiency in grinding tests.
[0083] The above results show that the vitrified binder obtained in Example 2 can soften and viscous flow under firing conditions of 980℃, and form a continuous bonding bridge between white corundum abrasive grains. The resulting ceramic abrasive has good structural integrity and mechanical properties.
[0084] Example 6 This embodiment provides a method for preparing ceramic abrasives using Pidgeon process magnesium slag-based vitrified binders, including the following steps: Provide the vitrified binder obtained in Example 3; Take 70 parts brown fused alumina abrasive, 30 parts silicon carbide abrasive, 15 parts vitrified binder, appropriate amount of polyvinyl alcohol (PVA, temporary binder), and appropriate amount of water by weight, mix them evenly to obtain the mixture. After the mixture is pressed into shape, it is dried at 90℃ for 10 h to obtain a dried green body. The dried blank is placed in a kiln and kept at 1020℃ for 2 hours; then cooled to room temperature in the kiln to obtain ceramic molds.
[0085] The ceramic abrasive obtained in this embodiment has a complete appearance, without cracks or deformation.
[0086] The flexural strength of the obtained ceramic abrasive was determined to be 72.3 MPa using the three-point bending method; its hardness was measured to be HRB 85.4 using a Rockwell hardness tester; and its bulk density was determined to be 2.29 g / cm³ using the Archimedes method. 3 The apparent porosity is 33.8%; the average linear expansion coefficient, measured by a thermal dilatometer, is 6.5 × 10⁻⁶ over the range of room temperature to 800℃. -6 / ℃; This ceramic abrasive combines the toughness of corundum abrasive and the sharpness of silicon carbide abrasive in grinding tests, and exhibits excellent grinding efficiency and surface finish.
[0087] The above results show that the vitrified binder obtained in Example 3 can form a stable bonding phase under sintering conditions of 1020℃, achieving effective bonding of brown corundum and silicon carbide abrasives. The resulting abrasive has good structural stability and mechanical properties.
[0088] Comparative Example 1 Provide the same batch of Pidgeon process magnesium smelting slag used in Example 2; By mass fraction, 100 parts of white corundum abrasive, 12 parts of the same batch of Pidgeon process magnesium smelting slag used in Example 2, 2 parts of dextrin, and an appropriate amount of water were mixed evenly to obtain a mixture; the Pidgeon process magnesium smelting slag was only subjected to crushing, homogenization, and drying treatment.
[0089] After the mixture is pressed into shape, it is dried at 80℃ for 12 h to obtain a dried green body. The dried blank is placed in a kiln and kept at 980℃ for 2 hours; then cooled to room temperature in the kiln to obtain ceramic molds.
[0090] The resulting ceramic abrasive exhibited obvious microcracks and localized cracking after firing. Its flexural strength, measured using the three-point bending method, was 32.6 MPa, its bulk density was 2.18 g / cm³, and its apparent porosity was 40.7%. Due to the significant cracking and uneven microstructure of the obtained ceramic abrasive, further Rockwell hardness and coefficient of thermal expansion tests were not performed.
[0091] Comparative Example 2 Provide the same batch of vitrified binder compound used in Example 2; Without undergoing 1420℃ melting and water quenching vitrification treatment, the vitrified binder compound is directly ball-milled to D90≤45μm to obtain an unvitrified binder.
[0092] Take 100 parts of white fused alumina abrasive, 12 parts of the above-mentioned unvitrified binder, 2 parts of dextrin, and an appropriate amount of water by weight, mix them evenly to obtain a mixture; After the mixture is pressed into shape, it is dried at 80℃ for 12 h to obtain a dried green body. The dried green body was placed in a kiln and held at 980℃ for 2 hours; then cooled to room temperature in the kiln to obtain a ceramic abrasive. The obtained ceramic abrasive was basically intact in appearance, but there were some small cracks in some areas, and the uniformity of the binder distribution was lower than that in Example 5. Its flexural strength was measured to be 48.9 MPa and its bulk density was 2.31 g / cm³ using the three-point bending method. 3 The apparent porosity is 38.5%.
[0093] Hydration stability test The Pidgeon process magnesium smelting slag pretreatment material used in Example 2 and the vitrified binder obtained in Example 2 were respectively mixed with a small amount of polyvinyl alcohol solution and pressed into cylindrical samples of the same size. After drying to constant weight, the initial dimensions were measured. The samples were completely immersed in deionized water for 72 h, and after removal, their appearance changes were observed and the linear expansion rate was measured.
[0094] The results are shown in Table 1.
[0095] Table 1. Hydration stability test results of the Pidgeon process magnesium smelting slag pretreated material and vitrified binder in the examples.
[0096] The results showed that the degree of hydration expansion of the Pidgeon process magnesium smelting slag was significantly reduced after batching and conditioning, melting and homogenization, and rapid quenching and vitrification. This indicates that the free CaO, MgO, and active calcium-magnesium-silica components in the original magnesium slag enter the glass network or undergo stabilization transformation after melting and vitrification, thereby effectively reducing its hydration activity and volume stability risks.
[0097] In summary, this application provides a vitrified binder based on Pidgeon process magnesium slag. This vitrified binder uses 25%–60% by mass of Pidgeon process magnesium smelting slag as the main calcium-magnesium-silica raw material, and synergistically incorporates 15%–40% silicon-containing raw material, 8%–28% boron-containing raw material, 3%–15% aluminum-containing raw material, and 2%–10% alkali metal modifier. This reconstructs the original CaO-MgO-SiO2 high-melting-point ternary system in the Pidgeon process magnesium smelting slag into a CaO-MgO-SiO2-Al2O3-B2O3-R2O multi-element eutectic system. The B2O3 introduced by the boron-containing raw material reduces the degree of glass network polymerization, and the R2O introduced by the alkali metal modifier provides free oxygen to cleave Si-O bonds. This synergistically lowers the liquid phase generation temperature of the vitrified binder to the mold firing range of 850℃–1100℃.
[0098] This application provides a method for preparing a vitrified binder based on Pidgeon process magnesium slag. The method involves high-temperature melting treatment to completely dissolve all crystalline mineral phases in the Pidgeon process magnesium smelting slag at the atomic scale and homogenize them with tempering components to form a homogeneous glass melt. Then, rapid cooling is applied to quickly freeze the high-temperature melt across the crystallization temperature range into a long-range disordered homogeneous glassy solid. This process incorporates hydration-active free CaO and free MgO from the Pidgeon process magnesium smelting slag with Ca... 2+ and Mg 2+ The ionic form of the substance is firmly fixed in the interstices of the silicon-oxygen tetrahedral network as a network modifier, thereby eliminating the risk of hydration swelling.
[0099] When this vitrified binder is applied to ceramic abrasives, the resulting ceramic abrasives exhibit comprehensive mechanical properties and firing stability that meet the requirements for industrial applications, demonstrating significant environmental, economic, and industrialization benefits.
[0100] Furthermore, one or more technical solutions in the embodiments of this application have at least the following technical effects or advantages: The embodiments of this application increase the amount of Pidgeon process magnesium smelting slag to 25% to 60% of the total raw material mass, realizing the large-scale resource utilization of Pidgeon process magnesium smelting slag. This can significantly reduce environmental problems such as land occupation, soil alkalization, groundwater pollution and air dust pollution caused by magnesium slag stockpiling. At the same time, it replaces natural mineral raw materials such as quartz, feldspar, limestone and talc in traditional ceramic binders, reducing the raw material cost of Pidgeon process magnesium slag-based vitrified binders.
[0101] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A vitrifying binder based on Pidgeon process magnesium slag, characterized in that, The raw materials for preparing the vitrified binder, by weight percentage, include: Pidgeon process magnesium smelting slag: 25%–60%, silicon-containing raw materials: 15%–40%, boron-containing raw materials: 8%–28%, aluminum-containing raw materials: 3%–15%, alkali metal modifier: 2%–10%, glass structure modifier: 0%–8%, crystallization modifier: 0%–5%.
2. The vitrified binder according to claim 1, characterized in that, The Pidgeon process magnesium smelting slag is the smelting slag produced during the Pidgeon process magnesium smelting; The silicon-containing raw materials include at least one of quartz powder, silicon micro powder, waste glass powder, and borosilicate glass powder; The boron-containing raw material includes at least one of boric acid, borax, boron oxide, and boron glass powder; The aluminum-containing raw material includes at least one of kaolin, alumina, bauxite, and pyrophyllite; The alkali metal modifier includes at least one of sodium carbonate, potassium carbonate, lithium carbonate, albite, and potassium feldspar. The glass structure modifier includes at least one of zinc oxide, talc, zirconium silicate, and calcium carbonate; The crystallization regulator includes at least one of zirconium oxide, titanium oxide, cerium oxide, lanthanum oxide, and yttrium oxide.
3. The vitrified binder according to claim 1, characterized in that, The oxide composition of the vitrified binder, by mass percentage, includes: SiO2: 35%–55%, B2O3: 8%–25%, Al2O3: 3%–15%, CaO: 10%–30%, MgO: 3%–15%, Na2O+K2O+Li2O: 1%–12%, ZnO+ZrO2+TiO2+rare earth oxides: 0%–10%, Fe2O3 ≤5%.
4. A method for preparing a Pidgeon process magnesium slag-based vitrified binder according to any one of claims 1 to 3, characterized in that, Includes the following steps: The Pidgeon process magnesium smelting slag is subjected to crushing, homogenization and drying processes in sequence to obtain magnesium slag pretreated material; The magnesium slag pretreated material, the silicon-containing raw material, the boron-containing raw material, the aluminum-containing raw material, and the alkali metal regulator are mixed to obtain a vitrified binder compound. The vitrified binder batch is melted to obtain calcium magnesium silicon borosilicate glass melt; The calcium-magnesium-silicon-boron-aluminum glass melt is vitrified to obtain a vitrified material; and, The vitrified material is dried, ground, and classified in sequence to obtain the Pidgeon process magnesium slag-based vitrified binder.
5. The method according to claim 4, characterized in that, It may also include: Before performing the melt treatment on the vitrified binder batch, the glass structure modifier and / or the crystallization modifier are added to the vitrified binder batch.
6. The method according to claim 4, characterized in that, The melting process includes: heating the vitrified binder compound to 1250°C–1500°C at a heating rate of 3°C / min–10°C / min, and melting it at a constant temperature of 1250°C–1500°C for 30 min–180 min; and / or, The drying temperature is 80℃~150℃; the drying time is 4h~12h; and / or, The particle size of the pretreated magnesium slag is ≤0.5mm; The moisture content of the pretreated magnesium slag material is <1%.
7. The method according to claim 4, characterized in that, The vitrification process includes: The calcium magnesium silicon boron aluminum glass melt is subjected to water quenching and rapid cooling treatment to obtain the vitrified material; Alternatively, the calcium-magnesium-silicon-boron-aluminum glass melt can be subjected to pressing, rapid cooling, and crushing processes in sequence to obtain the vitrified material.
8. The method according to any one of claims 4 to 7, characterized in that, The particle size D of the Pidgeon process magnesium slag-based vitrified binder 50 The particle size ranges from 3μm to 20μm, with a particle size D. 90 ≤45μm.
9. The application of the Pidgeon process magnesium slag-based vitrifying binder according to any one of claims 1 to 3, characterized in that, The Pijang process magnesium slag-based vitrified binder is used to prepare ceramic molds; The method for using the Pidgeon process magnesium slag-based vitrified binder to prepare ceramic molds includes the following steps: The vitrified binder, abrasive, and temporary binder are mixed to obtain a mixture; The mixture is sequentially pressed and dried to obtain a dried green body; and, The dried blank is then calcined to obtain a ceramic abrasive.
10. The application according to claim 9, characterized in that, The calcination process includes: heating the dried green body to 850℃~1100℃, and holding it at a constant temperature of 850℃~1100℃ for 1h~4h; and / or, The vitrified binder accounts for 6% to 25% of the mass of the abrasive; and / or, The temporary binder is present in an amount of 1% to 5% of the abrasive mass; and / or, The abrasive includes at least one of corundum abrasive and silicon carbide abrasive; and / or, The temporary binder includes at least one of dextrin, polyvinyl alcohol, carboxymethyl cellulose, and lignin sulfonate.